Literature Review: Factors Affecting Antenatal Care Visits - Winancy, Winancy; Munawarah, Raudhatul (Journal of Economics and Public Health, 2025)
Antenatal care (ANC) visits play a crucial role in reducing maternal and neonatal morbidity and mortality. However, the utilization of ANC services remains inconsistent and is influenced by multiple interrelated factors. This study aims to comprehensively examine the factors affecting ANC visits through a literature review approach. The literature search was conducted using PubMed, Google Scholar, and ScienceDirect databases, covering publications from 2020 to 2025. Articles were selected through a systematic screening process based on predefined inclusion and exclusion criteria. From the four articles that met the inclusion criteria, a number of consistent patterns and themes emerged. The selected studies were analyzed using a narrative synthesis to identify recurring themes and patterns. The findings indicate that ANC visits are shaped by several key determinants, including maternal knowledge, family support particularly from husbands accessibility of health facilities, socio-economic conditions, and geographical barriers. In addition, risk perception of pregnancy and the perceived quality of health services also influence mothers’ decisions to attend regular ANC visits. These results highlight that ANC utilization is not merely an individual behavior, but rather a product of the interaction between personal, social, and structural factors. From a theoretical perspective, this study reinforces the multidimensional health behavior framework. In terms of policy and practice, the findings emphasize the importance of comprehensive interventions that integrate family involvement, community-based strategies, and improved access to maternal health services.